2016
DOI: 10.1371/journal.pone.0147767
|View full text |Cite
|
Sign up to set email alerts
|

One Dose of Staphylococcus aureus 4C-Staph Vaccine Formulated with a Novel TLR7-Dependent Adjuvant Rapidly Protects Mice through Antibodies, Effector CD4+ T Cells, and IL-17A

Abstract: A rapidly acting, single dose vaccine against Staphylococcus aureus would be highly beneficial for patients scheduled for major surgeries or in intensive care units. Here we show that one immunization with a multicomponent S. aureus candidate vaccine, 4C-Staph, formulated with a novel TLR7-dependent adjuvant, T7-alum, readily protected mice from death and from bacterial dissemination, both in kidney abscess and peritonitis models, outperforming alum-formulated vaccine. This increased efficacy was paralleled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
(55 reference statements)
1
40
0
Order By: Relevance
“…We have previously shown that the 4C-Staph formulation is effective in reducing S. aureus systemic infection in different murine models21222324. Immunization of mice with this formulation was associated in the present model with reduction of the bacterial load both in knee joints and kidneys (Fig.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…We have previously shown that the 4C-Staph formulation is effective in reducing S. aureus systemic infection in different murine models21222324. Immunization of mice with this formulation was associated in the present model with reduction of the bacterial load both in knee joints and kidneys (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…This may positively affect the control of the infection not only because a greater number of viable B cells is present in situ and produces specific IgG, but also because the antigen presenting activity may be exerted more efficiently70. The second change that we observed concerned the specific CD4+ T cells induced by vaccination with 4C-Staph, and which we have previously shown to protect mice against septic death2324. In fact, we observed that, in mice immunized with the 4C-staph formulation, a significantly higher number of CD4+ T effector memory lymphocytes was present in the knee joints as compared to the blood, and that these cells were mainly associated with the presence of Th0-Th2 but also of Th1-like cytokines, as was to be expected on the basis of the alum adjuvant used (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…54 In addition, a separate 4 component S. aureus vaccine (4C-Staph) formulated with a TLR7-dependent adjuvant is under development. 55 …”
Section: Vaccines In Late Stage Development With Potential To Reduce Amrmentioning
confidence: 99%